Diagnostic and therapeutic utility of SpyGlass® peroral cholangioscopy in intraductal biliary disease: Single‐center, retrospective, cohort study. Issue 4 (11th December 2014) - Tieu, Alan H.; Kumbhari, Vivek; Jakhete, Neha; Onyimba, Frances; Patel, Yuval; Shin, Eun Ji; Li, Zhiping
<x xml:space="preserve">Abstract</x> Background and Aim SpyGlass® cholangiopancreatoscopy system has shown early success in aiding diagnosis and management of pancreaticobiliary diseases. We aimed to assess the technical success, clinical success, diagnostic yield, therapeutic yield, and safety of the SpyGlass® system at a single institution. Methods A retrospective, single‐center review of consecutive patients who underwent endoscopic retrograde cholangiopancreatography with SpyGlass® between January 2008 and August 2013 for a variety of indications. Technical success was defined as the procedure being completed as planned. Clinical success was defined as a successful outcome using diagnostic, clinical, laboratory, or imaging evidence. Results SpyGlass® cholangioscopy was carried out in 88 patients (49 females, mean age 56.9 ± 15.5 years). Indications were diagnostic in 67 and therapeutic in 21. Overall, technical success was seen in 87.5% and clinical success in 77.3%. Thirty‐nine patients with indeterminate biliary stricture had technical and clinical success rates of 92.3% and 74.4%, respectively. In this subgroup, malignancy was ultimately diagnosed in 13 with 12 patients diagnosed by SpyGlass® and confirmed by surgical specimens in 12/12 cases; positive predictive value 100%). In the 23 remaining patients with indeterminate biliary strictures, one was later found to have malignancy (negative predictive value 95.8%) after 1 year of follow up. In the 13 therapeutic cases of stone removal, technical and clinical success was seen in 77.0% for both. Overall, adverse events were seen in 15.9%. Conclusions SpyGlass® demonstrated acceptable technical and clinical success rates in both diagnostic and therapeutic procedures. In particular, it allows for an accurate rate of diagnosis of indeterminate biliary strictures.